Alcohol consumption in an empty nest - Francesco Scervini; Serena Trucchi (Cardiff University, Cardiff Business School, 2024)
Alcohol consumption among older adults has been drawing public health interest due to the rising use of alcohol in the growing elderly population. This paper adds to the understanding of alcohol consumption in later life by investigating the impact of a specific life event: the transition to an empty nest, when adult children leave the parental home. Our findings show a significant increase in alcohol consumption in an empty nest, equivalent to approximately one additional drink every one to three weeks. This change is characterised by more regular drinking patterns and a modest rise in daily intake. The groups most affected by this change include couples, individuals with high income, those actively employed, and respondents aged 45-60. We also provide evidence on the mechanisms underlying this relationship, supporting a key role of relaxation and changes in time use.
Keywords: D1; I12; J14; 330; Empty nest; alcohol consumption; longitudinal data